1987
DOI: 10.1159/000234367
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Oxatomide on Intracellular Ca Mobilization, Ca Uptake and Histamine Release, Using Rat Peritoneal Mast Cells

Abstract: Oxatomide at concentrations of 0.01––10 μM inhibited not only an increase in 45Ca uptake but also the intracellular Ca2+ release induced by compound 48/80 in rat peritoneal mast cells. At higher concentrations, ketotifen or other calcium antagonists caused similar inhibitory effects. However, the inhibitory effect of oxatomide on the 45Ca uptake into rat neonatal heart cells was much weaker than that of verapamil. Through image processing of quin 2-stained mast cells, it was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…We have previously reported that oxatomide is effective in the same concentration range in inhibiting both increases in 4 5 C a uptake and intracellular Ca2+ release induced by compound 48/80 in rat peritoneal mast cells (7). Thus, it seems possible that the inhibition of Ca2+ incorporation into guinea pig lung mast cells and of Ca2+ releasc from the intracellular Ca store of rat mast cells caused by epinastine takes place in almost the same concentration range, which is also effective in inhibiting histamine release.…”
Section: Disc Us S I 0 Nmentioning
confidence: 89%
See 1 more Smart Citation
“…We have previously reported that oxatomide is effective in the same concentration range in inhibiting both increases in 4 5 C a uptake and intracellular Ca2+ release induced by compound 48/80 in rat peritoneal mast cells (7). Thus, it seems possible that the inhibition of Ca2+ incorporation into guinea pig lung mast cells and of Ca2+ releasc from the intracellular Ca store of rat mast cells caused by epinastine takes place in almost the same concentration range, which is also effective in inhibiting histamine release.…”
Section: Disc Us S I 0 Nmentioning
confidence: 89%
“…Intracellular Ca2+ conccntration was measured according to the mcthod described in a previous paper (7). In bricl', rat peritoneal mast cells washcd with PBS were suspended in 5 pM of quin 2/AM, and incubatcd for 60 min at 37°C.…”
Section: Measurement Of Intraccllular Ca2+ Conccntration Of Rat Pcrmentioning
confidence: 99%
“…Histamine release from lung pieces of actively sensitized guinea pigs was measured according to the method previously described [17]. Male Hartley guinea pigs, weighing 350-400 g, were immunized according to the method of Mota et al [18].…”
Section: Histamine Release From Lung Samples Of Sensitized Guinea Pigsmentioning
confidence: 99%
“…It is considered that the inhibitory effects on chemical media tors, such as histamine and leukotrienes, of oxatomide [6,7] and the inhibitory effect on histamine release of oxatomide [2][3][4][5] were exhibited by its intranasal administration of ox atomide nasal spray. Accordingly, oxatomide nasal spray is expected to be effective against two of the three main symp toms of allergic rhinitis, i.e., rhinorrhea and nasal conges tion; the latter is due to edema caused by plasma leakage.…”
Section: Discussionmentioning
confidence: 99%